DIGITAL DISTRUST AS A PREDICTOR OF ONLINE-TRANSACTIONS ACCEPTANCE (OTA) AMONG YOUTH IN EDO STATE, NIGERIA - Eromosele Felix , Obainoke (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
The growing trend of technological innovations enabling the possibility of digital marketing has impacted the buying and selling process. However, consumers' unbridled enthusiasm for the digital market is moderated by worries about privacy, data breaches, and trust. The public has a growing awareness of the prevalence of digital manipulations. Thus, the present study examines the effect of digital distrust on attitudes toward online shopping. Two hundred and twenty-eight youths from three public tertiary institutions in Edo state participated in the study. The respondents completed a self-report measure of digital distrust and attitude towards online shopping. The simple regression analysis revealed that digital distrust statistically significantly predicted the respondent's attitudes towards online shopping F (1,226), 36.57, P<.000. More so, digital distrust contributed 32.1% of the variance in the attitudes towards online shopping. The study concludes that digital distrust is a positive predictor of online shopping. The implications of the study are discussed.